2010
DOI: 10.1089/neu.2010.1425
|View full text |Cite
|
Sign up to set email alerts
|

Post-Traumatic Hydrocephalus after Decompressive Craniectomy: An Underestimated Risk Factor

Abstract: The incidence of post-traumatic hydrocephalus (PTH) has been reported to be 0.7-51.4%, and we have frequently observed the development of PTH in patients undergoing decompressive craniectomy (DC). For this reason we performed a retrospective review of a consecutive series of patients undergoing DC after traumatic brain injury (TBI). From January 2006 to December 2009, 41 patients underwent DC after closed head injury. Study outcomes focused specifically on the development of hydrocephalus after DC. Variables d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
116
5
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 153 publications
(130 citation statements)
references
References 20 publications
6
116
5
2
Order By: Relevance
“…Injury severity is another impact factor for hydrocephalus. In a multivariate analysis, Honeybul et al found that maximum ICP prior to decompression (p=0.012) and admission Glasgow Coma Score (GCS) (p=0.009), which are indicators of injury severity, are significant independent risk factors for development of hydrocephalus after DC, but they found no relationship between the craniectomy margin and hydrocephalus 11 , which differs from a report by De Bonis et al 28 . Their results suggest that damage to the CSF drainage pathways contributes to the primary brain injury, rather than the craniectomy margin, as a factor responsible for hydrocephalus.…”
Section: Mechanisms Of Hydrocephalus After DCmentioning
confidence: 82%
See 2 more Smart Citations
“…Injury severity is another impact factor for hydrocephalus. In a multivariate analysis, Honeybul et al found that maximum ICP prior to decompression (p=0.012) and admission Glasgow Coma Score (GCS) (p=0.009), which are indicators of injury severity, are significant independent risk factors for development of hydrocephalus after DC, but they found no relationship between the craniectomy margin and hydrocephalus 11 , which differs from a report by De Bonis et al 28 . Their results suggest that damage to the CSF drainage pathways contributes to the primary brain injury, rather than the craniectomy margin, as a factor responsible for hydrocephalus.…”
Section: Mechanisms Of Hydrocephalus After DCmentioning
confidence: 82%
“…Lee et al reported a 41.2% incidence of hydrocephalus in patients who suffer from malignant middle cerebral artery infarction and underwent DC 27 . De Bonis and colleagues found a lower incidence of hydrocephalus after DC (34.5%) according to more strict criteria: radiographic evidence of progressive ventricular dilatation with an Evan index .0.3, associated with narrowed CSF spaces at the convexity on serial CT imaging 28 . Others defined hydrocephalus as progressive ventricular dilatation with trans-ependymal edema, together with (1) the presence of either clinical deterioration or failure to make neurological progress over time, and (2) some evidence of clinical improvement after insertion of a ventriculo-peritoneal shunt (V-P shunt).…”
Section: Incidence Of Hydrocephalus After DCmentioning
confidence: 99%
See 1 more Smart Citation
“…One study that may explain this discrepancy was performed by De Bonis et al, 24 who reported their experience with posttraumatic hydrocephalus in patients who had undergone decompressive hemicraniectomy after traumatic brain injury. They analyzed the area of craniotomy and the distance of the craniotomy from the midline.…”
Section: Ventriculomegaly Associated With Craniectomymentioning
confidence: 99%
“…They hypothesized, based on the Starling resistor concept, that during each cardiac cycle in which extracellular fluid is produced during systole and absorbed in diastole, an imbalance between the production and absorption of extracellular fluid in favor of absorption would cause a decrease in brain parenchyma volume and consequently increase the size of the ventricles. 24 Thus in patients with craniectomies too close to the midline, the loss of CSF pressure surrounding the cortical draining veins in diastole would cause an increase in venous outflow. In turn, cerebral venous overdrainage would cause an increase in extracellular fluid absorption, leading to a loss of brain parenchyma volume and ventriculomegaly.…”
Section: Ventriculomegaly Associated With Craniectomymentioning
confidence: 99%